Upaya Peningkatan Kualitas Sumber Daya Manusia Guru Dan Karyawan di MAN 2 Manggarai Tahun Pelajaran 2023/2024 - Mansur Amriatul (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
The first step to create quality educational outcomes requires attention to the quality of the components of the education system that are human resources. The components of the education system that are human resources include educators / teachers. Thus, within the scope of Madrasah the response to face the era of globalization and nation building is carried out by striving to improve the quality of human resources of teachers and Madrasah employees in providing services. So that later the expected educational goals can be achieved well, especially in preparing qualified cadres of the nation, able to compete and able to face the challenges of the times in the future. Based on the presentation of the research report and the discussion of the research findings that the author has described in the previous chapter, it can be concluded that the quality of human resources (HR) in MAN 2 Manggarai Manggarai Regency can be said to be quite good, but still needs to be developed and improved. This is because the discipline of teachers and employees is still lacking, in terms of placement / distribution of tasks in this school there are still teachers who hold subjects that are not in accordance with their respective fields. In terms of discipline in the implementation of learning service duties, MAN 2 Manggarai teachers of Manggarai Regency have used learning tools in accordance with the provisions and have followed the development of education well, especially regarding learning problems.